Komunikasi Termediasi Penipuan dengan Modus Business Email Compromise - Tri Andriyanto (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2022)
Business Email Compromise (BEC) has become a new mode of cyber crime in the form of phishing emails to targeted individuals or corporations for financial benefits. This article discusses the concept of BEC in the scope of mediated communication and persuasion from the perpetrator to the victim and is related to the theory of Computer-Mediated Communication and the Elaboration Likelihood Model. The research method uses a qualitative approach with a study of email documentation related to BEC and interviews with a number of primary sources involved in handling BEC cases. The results of the analysis show the development of communication in BEC which goes through the phases of impersonal, interpersonal, and hyperpersonal communication. The results of the analysis also show that there was an attempt at persuasion from the BEC perpetrators by directing the victim on a peripheral route with one or a few cues so that there would be a change in attitude in the form of being willing to transfer a certain amount of funds to the account provided by the perpetrator. If the peripheral route is not enough to convince the victim, the BEC perpetrator will use the central route by building persuasion from aspects of motivation, ability, and strong arguments.